Game-Based Learning for Arabic Vocabulary Development: The Implementation of “Mughamarah fil ‘Arabiyyah” in a Junior High School - Nurul Fahmi; Muhammad Kamal bin Abdul Hakim; Farida Nazriyah; Mutiara Fitri Sa'diah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Vocabulary mastery plays a fundamental role in Arabic language learning, particularly at the secondary school level where students begin to develop more complex language skills. However, vocabulary instruction in many schools remains dominated by teacher-centered and memorization-based approaches, which often result in low student engagement and limited retention. This study aimed to examine the effectiveness of Mughamarah fil ‘Arabiyyah, a non-digital game-based learning medium, in improving students’ Arabic vocabulary mastery. The study employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The participants consisted of 12 eighth-grade students at SMP Bina Dakwah, Bogor, selected through purposive sampling. Data were collected through a 20-item Arabic vocabulary test administered before and after the implementation of the game-based learning intervention. Descriptive statistics and a paired sample t-test were used to analyze the data. The results revealed a significant improvement in students’ vocabulary mastery, with the mean score increasing from 68.18 in the pretest to 90.67 in the posttest. These findings indicate that Mughamarah fil ‘Arabiyyah is an effective instructional medium for enhancing Arabic vocabulary learning, particularly in educational contexts with limited technological resources. This study contributes to Arabic language pedagogy by providing empirical evidence on the effectiveness of non-digital game-based learning media and offers practical insights for teachers seeking engaging vocabulary instruction strategies in resource-limited classrooms.